Characterization of atrial fibrillation in real-world patients: testing the 4S-AF scheme in the Spanish and French cohorts of the EORP-AF Long-Term General Registry. Issue 2 (10th August 2021) - Rivera-Caravaca, José Miguel; Piot, Olivier; Roldán-Rabadán, Inmaculada; Denis, Arnaud; Anguita, Manuel; Mansourati, Jacques; Pérez-Cabeza, Alejandro; Marijon, Eloi; García-Seara, Javier; Leclercq, Christophe; García-Bolao, Ignacio; Lellouche, Nicolas; et al.
Abstract: Aims: The 4S-AF scheme [Stroke risk, Symptom severity, Severity of atrial fibrillation (AF) burden, Substrate severity] has recently been described as a novel approach to in-depth characterization of AF. We aim to determine if the 4S-AF scheme would be useful for AF characterization and provides prognostic information in real-world AF patients. Methods and results: The Spanish and French cohorts of the EORP-AF Long-Term General Registry were included. The baseline 4S-AF scheme was calculated and related to the primary management strategy (rhythm or rate control). Follow-up was performed at 1-year with all-cause mortality and the composite of ischaemic stroke/transient ischaemic attack/systemic embolism, major bleeding, and all-cause death, as primary endpoints. A total of 1479 patients [36.9% females, median age 72 interquartile range (IQR 64–80) years] were included. The median 4S-AF scheme score was 5 (IQR 4–7). The 4S-AF scheme, as continuous and as categorical, was associated with the management strategy decided for the patient (both P < 0.001). The predictive performances of the 4S-AF scheme for the actual management strategy were appropriate in its continuous [c-index 0.77, 95% confidence interval (CI) 0.75–0.80] and categorical (c-index 0.75, 95% CI 0.72–0.78) forms. Cox regression analyses showed that 'red category' classified patients in the 4S-AF scheme had a higher risk of all-cause death (aHR 1.75, 95% CI 1.02–2.99) and composite outcomes (aHR 1.60, 95% CI 1.05–2.44). Conclusion: Characterization of AF by using the 4S-AF scheme may aid in identifying AF patients that would be managed by rhythm or rate control and could also help in identifying high-risk AF patients for worse clinical outcomes in a 'real-world' setting.